The Battle for the Soul - Crawford, R. author. aut Link
XII, 254 p.
Keywords: Do we all possess a soul? If so, what is it? Can it be defined? Crawford argues that it is important that we have a soul because if it is immortal then we can hope for life after death. But some religions insist that it is the resurrection of the body which is vital.